Aldosterone status associated with insulin resistance in patients with heart failure—data from the ALOFT study. Issue 23 (26th August 2009) - Freel, E M; Tsorlalis, I K; Lewsey, J D; Latini, R; Maggioni, A P; Solomon, S; Pitt, B; Connell, J M C; McMurray, J J V
Abstract : Background: Aldosterone has a key role in the pathophysiology of heart failure. In around 50% of such patients, aldosterone "escapes" from inhibition by drugs that interrupt the renin-angiotensin axis; such patients have a worse clinical outcome. Insulin resistance is a risk factor in heart failure and cardiovascular disease. The relation between aldosterone status and insulin sensitivity was investigated in a cohort of heart failure patients. Methods: 302 patients with New York Heart Association (NYHA) class II-IV heart failure on conventional therapy were randomised in the ALiskiren Observation of heart Failure Treatment study (ALOFT), designed to test the safety of a directly acting renin inhibitor. Plasma aldosterone and 24-hour urinary aldosterone excretion, as well as fasting insulin and homeostasis model assessment of insulin resistance (HOMA-IR) were measured. Subjects with aldosterone escape and high urinary aldosterone were identified according to previously accepted definitions. Results: 20% of subjects demonstrated aldosterone escape and 34% had high urinary aldosterone levels. At baseline, there was a positive correlation between fasting insulin and plasma (r = 0.22 p<0.01) and urinary aldosterone(r = 0.19 p<0.03). Aldosterone escape and high urinary aldosterone subjects both demonstrated higher levels of fasting insulin (p<0.008, p<0.03), HOMA-IR (p<0.06, p<0.03) and insulin-glucose ratios (p<0.006, p<0.06) when compared to low aldosterone counterparts. All associations remained significant when adjusted for potential confounders. Conclusions: This study demonstrates a novel direct relation between aldosterone status and insulin resistance in heart failure. This observation merits further study and may identify an additional mechanism that contributes to the adverse clinical outcome associated with aldosterone escape.